The objectives and intents of Islamic Law as a paradigm of development strategies and policies - E-Elahi, Mohammad Manzur; Osmani, Noor Mohammad (International Islamic University Malaysia, 2011)
The paper presents the theory of objectives and intents of Islamic law termed as Maqasid al-Shari`ah al-Islamiyyah as a vision through which present and future changes and development of the Ummah can be defined, negotiated, led and persuaded.The theme presented in the paper is that the knowledge of the Objectives of Islamic Law can play an important role as a universal paradigm in enhancing the abilities and qualities of the Ummah to reach a positive change and development out of the present situation. But there is a need to review the framework based on the knowledge of the Objectives of Islamic Law in order to ensure its effectiveness in providing the necessary principles, methods and guidelines required in the processes of development strategy. Thus the paper suggests the ways of restoring back the sense of dynamism to the objective approach of Islamic law in creating the methodological, social, educational and epistemological and cultural frameworks as a paradigm of development strategies, policies and processes for the betterment of the contemporary Muslim Ummah.